Les outils de représentation graphique de l’espace relationnel face au secret : le cas des conspirateurs du 19 août 1820 - Vivien Faraut (Les Cahiers de Framespa)
Often neglected by historians working on the opponents to the restored Bourbons, the August 19, 1820 conspiracy is a founding moment for the armed opposition. Indeed, the magnitude of the crowd mobilized and of the plan developed by former soldiers of the Grande Armée are unheard of in the early years of the French Restoration. Its impact exceeds the sole political sphere since the Chambre des Pairs becomes a Court of justice. This conspiracy and its consequences are addressed through the tools of visualization of social networks. The purpose is to analyse the ways in which the different protagonists get organized and according to what timeline. But these tools are also an opportunity to examine the perception that the authorities have of the participants in the conspiracy and understand on what criteria the indictment is built.